High-content analysis of factors affecting gold nanoparticle uptake by neuronal and microglial cells in culture. Issue 37 (8th September 2016) - Stojiljković, A.; Kuehni-Boghenbor, K.; Gaschen, V.; Schüpbach, G.; Mevissen, M.; Kinnear, C.; Möller, A.-M.; Stoffel, M. H.
Abstract : High-content analysis is a powerful tool to quantitate the impact of various factors affecting the uptake of untagged gold nanoparticles. Abstract : Owing to their ubiquitous distribution, expected beneficial effects and suspected adverse effects, nanoparticles are viewed as a double-edged sword, necessitating a better understanding of their interactions with tissues and organisms. Thus, the goals of the present study were to develop and present a method to generate quantitative data on nanoparticle entry into cells in culture and to exemplarily demonstrate the usefulness of this approach by analyzing the impact of size, charge and various proteinaceous coatings on particle internalization. N9 microglial cells and both undifferentiated and differentiated SH-SY5Y neuroblastoma cells were exposed to customized gold nanoparticles. After silver enhancement, the particles were visualized by epipolarization microscopy and analysed by high-content analysis. The value of this approach was substantiated by assessing the impact of various parameters on nanoparticle uptake. Uptake was higher in microglial cells than in neuronal cells. Only microglial cells showed a distinct size preference, preferring particles with a diameter of 80 nm. Positive surface charge had the greatest impact on particle uptake. Coating with bovine serum albumin, fetuin or protein G significantly increased particle internalization in microglial cells but not in neuronal cells. Coating with wheat germ agglutinin increased particle uptake in both N9 and differentiated SH-SY5Y cells but not in undifferentiated SH-SY5Y cells. Furthermore, internalization was shown to be an active process and indicators of caspase-dependent apoptosis revealed that gold nanoparticles did not have any cytotoxic effects. The present study thus demonstrates the suitability of gold nanoparticles and high-content analysis for assessing numerous variables in a stringently quantitative and statistically significant manner. Furthermore, the results presented herein showcase the feasibility of specifically targeting nanoparticles to distinct cell types.